Forme des territoires communaux et structure du bâti dans les cantons de Vaud et de Neuchâtel - Daniel Glauser (In Situ)
In French-speaking Switzerland, the characteristic topography of the landscape, between the mountain ranges of the Jura and the Alps, along with the history of how these landscapes were peopled, have given rise to a wide variety of forms of settlement. In the cantons of Vaud and Neufchatel in particular, there are landscapes of mixed pasture and woodland (bocage) as well as territories characterised by the collective three-field system with open-field farms. The villages too are structured according to a broad variety of patterns: horizontal linear structures, structures going up the slope with branches going off at angles, structures with radial patterns leading off from a central point or from a ring. Dispersed rural dwellings also follow different models: small hamlets with individual farms or with organisations in honeycomb patterns or bands of property.